O fazer de um formigueiro: o MTST, os sem teto e a ocupação povo sem medo em Fortaleza - Vieira, Leonardo Anderson Ricardo (2017)
I study the Occupation Povo SemMedo (OPSM), which occurred on a terrain along the Avenida Estrada da Urucutuba, in the BomJardim district, located in the perifery of Fortaleza, directed by the Homeless Workers Movement (MTST). I tried to understand how the social relations between the participants of the occupation had been produced and reproduced and in order to describe it in order to interpret it, I had as a guideline what led to the construction of three thousand black tarpaulins shacks, built from the 20th of May 2016. Some of these remained until August 2017. From a socio-anthropological perspective, through a militant observation, carried out between July 2014 and July 2017, I present the results of a work of observation, approximation and later participation with the MTST, coupled with semi-structured interviews and bibliographic discussion. Throughout the research, two hypotheses have emerged. The first one is that the practices of the MTST, like its model of organization and political method, directly affect the daily occupation and the formation of identities of the occupiers. The second hypothesis refers to the social similarities among those who occupy, represent a portion of those who lives from work, but are unable to obtain the means necessary for having access to decent housing.